2016
DOI: 10.1128/aac.02143-15
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aminoglycoside Resistance Transposons and Transposon-Derived Circular Forms Detected in Carbapenem-Resistant Acinetobacter baumannii Clinical Isolates

Abstract: Acinetobacter baumannii has emerged as an important opportunistic pathogen equipped with a growing number of antibiotic resistance genes. Our study investigated the molecular epidemiology and antibiotic resistance features of 28 consecutive carbapenem-resistant clinical isolates of A. baumannii collected throughout Sweden in 2012 and 2013. The isolates mainly belonged to clonal complexes (CCs) with an extensive international distribution, such as CC2 (n = 16) and CC25 (n = 7). Resistance to carbapenems was rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 64 publications
3
44
1
3
Order By: Relevance
“…WGS revealed that plasmid pAB-MAL-1 was 9,810 bp in size and belonged to the GR2 plasmid family. This plasmid was 99% identical to the recently published pA105-2 plasmid (GenBank accession number KR535993.1) recovered from an A. baumannii strain of ST636 (18). It showed strong similarity with plasmid p2ABST25 (GenBank accession number AEPA01000396.1) (19), differing only by the insertion of ISAba31 upstream of the bla OXA-72 gene (Fig.…”
Section: Resultssupporting
confidence: 55%
“…WGS revealed that plasmid pAB-MAL-1 was 9,810 bp in size and belonged to the GR2 plasmid family. This plasmid was 99% identical to the recently published pA105-2 plasmid (GenBank accession number KR535993.1) recovered from an A. baumannii strain of ST636 (18). It showed strong similarity with plasmid p2ABST25 (GenBank accession number AEPA01000396.1) (19), differing only by the insertion of ISAba31 upstream of the bla OXA-72 gene (Fig.…”
Section: Resultssupporting
confidence: 55%
“…Recently, the AbGRI3-2 structure that includes both Tn 6180 and Tn 6179 was found in the isolate A071 (GenBank accession number KT317075) and named Tn 6279 35 . This study also reported that circular TU forms of AbGRI3-2 (Tn 6180 and Tn 6179 with only two copies of IS 26 ) as well as just AbGRI3-1 (Tn 6180 with one copy of IS 26 ) could be detected by PCR in this isolate.…”
Section: Resultsmentioning
confidence: 52%
“…A. baumannii constitutes an increasing threat to hospitalized patients worldwide due to its high predisposition to nosocomial transmission and failure to respond to antimicrobial treatment due to rapid acquisition of multidrug resistance [2]. This resistance includes non-susceptibility to carbapenems, and hence the bacteria are called carbapenem-resistant A. baumannii (CRAB).…”
Section: Introductionmentioning
confidence: 99%
“…The most common lineages (ICL1-3) were initially reported in Europe and the United States, but later also in several countries in other parts of the world [15]. According to studies conducted in several European countries, the majority of CRAB outbreaks in that region have been associated with ICL2 isolates harbouring the oxacillinase bla OXA-23 -like carbapenemase gene [2,12]. Epidemiological investigations have described dissemination of A. baumannii isolates belonging to clonal complex 92 (CC92), corresponding to ICL2, in two hospitals in northern Iran [14,16].…”
Section: Introductionmentioning
confidence: 99%